Adaptable ox-carts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The number of working pairs of oxen in Sierra Leone has increased from 50 to around 1100 in the ten years that ODA Work Oxen Proiect has been in operation - and now animal-drawn transport is taking off in a big way, too. Oxcarts, sent to Sierra...